Absence of evidence is not evidence of absence: Nanopore sequencing and complete assembly of the European lobster (Homarus gammarus) mitogenome uncovers the missing nad2 and a new major gene cluster duplication - Gan, Han Ming; Grandjean, Frédéric; Jenkins, Tom; Austin, Christopher Mervyn (BMC Genomics, 2019)
International audience